Co3O4 Catalysts on CeO2-ZrO2 Supports and Co3O4-CeO2 Catalysts on Al2O3/SiO2 Supports for the Oxidation of Propylene - Tien The Nguyen; Phuong Thi Mai Pham; Thang Minh Le; Isabel Van Driessche (Journal of Chemistry)
Different compositions of Co3O4 catalysts on CeO2-ZrO2 solid solution (Ce0.9Zr0.1O2 and Ce0.8Zr0.2O2) have been studied for the oxidation of propylene. The optional amount of Co3O4 active phase on CeO2-ZrO2 support of 30 wt% was found. The mixed Co3O4-CeO2-ZrO2 with the same composition of the optimal supported ones showed approximately the same activity, which was not higher than the activity of the mixed Co3O4-CeO2 catalyst. Catalytic activities of mixed Co3O4-CeO2 with different loading contents supported on high surface area supports (Al2O3, SiO2) were then measured. The optimal composition of active phase was still 30 wt% but the minimum temperature of the highest activity increased to above 300°C due to the inert nature influence of the support.